Tropical Cyclone Intensity Estimation by Feature Extraction Techniques using Satellite Imagery - Kar, Chinmoy (Informatica, 2024)
This article provides an overview of the author's doctoral dissertation entitled "Intensity Estimation of Tropical Cyclones by Feature Extraction Techniques". The dissertation introduces feature extraction techniques applied to satellite images of tropical cyclones to extract meaningful features. Additionally, the dissertation explores the use of various machine learning classifiers to determine the intensity class of a tropical cyclone based on these features.